MEDIA DAN PERSPEKTIF FEMINIS - Nahdatunnisa Asry (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2018)
During this time women were the main objects of the media. The main discussion for feminists is the equality between men and women. Observer of women's issues and the media must join hands to jointly give birth to healthy readers without being filled with negative opinions and assumptions but seeing the problem in a balanced manner. On the other hand women must be able to maintain a way of life that is in accordance with the norm. the importance of good cooperation between observers of women's issues and the media is necessary, monitoring the media that often contains news that tends to be discriminatory and stereotypes of women needs to be done. In addition, the transfer of knowledge to the media individually is primarily an issue of equality to give birth to women's perspective journalism.KeywordMedia; Feminism